Climate Sensitivity of Peatland Methane Emissions Mediated by Seasonal Hydrologic Dynamics. Issue 17 (2nd September 2020) - Feng, Xue; Deventer, M. Julian; Lonchar, Rachel; Ng, G. H. Crystal; Sebestyen, Stephen D.; Roman, D. Tyler; Griffis, Timothy J.; Millet, Dylan B.; Kolka, Randall K.
Abstract: Peatlands are among the largest natural sources of atmospheric methane (CH4 ) worldwide. Peatland emissions are projected to increase under climate change, as rising temperatures and shifting precipitation accelerate microbial metabolic pathways favorable for CH4 production. However, how these changing environmental factors will impact peatland emissions over the long term remains unknown. Here, we investigate a novel data set spanning an exceptionally long 11 years to analyze the influence of soil temperature and water table elevation on peatland CH4 emissions. We show that higher water tables dampen the springtime increases in CH4 emissions as well as their subsequent decreases during late summer to fall. These results imply that any hydroclimatological changes in northern peatlands that shift seasonal water availability from winter to summer will increase annual CH4 emissions, even if temperature remains unchanged. Therefore, advancing hydrological understanding in peatland watersheds will be crucial for improving predictions of CH4 emissions. Plain Language Summary: Methane (CH4 ) emissions from wetlands are the largest natural source of atmospheric CH4 worldwide and are expected to increase under global warming. Because of a scarcity of field observations, we do not yet know how wetland CH4 emissions will be affected by future climates and under what conditions. In this study, we use a newly developed long‐term data set of CH4 flux measurements at a northern peatland to demonstrate the importance of seasonal water availability in controlling the sensitivity of CH4 emission increase to soil temperature. Our results suggest that a shift in water availability from winter to summer may result in higher annual CH4 emissions, even if soil temperatures remain the same. Key Points: A newly developed long‐term data set of methane (CH4 ) flux measurements at a northern peatland is analyzed Seasonal water availability is shown to control the sensitivity of CH4 emissions to increase in soil temperature Shifting water availability from winter to summer may result in higher annual CH4 emissions, even if soil temperatures remain the same